Measuring secure software development awareness and usage among software developers - Maher, Zulfikar Ahmad; Depar, M. H.; Memon, M.; Koondhar, Muhammad Yaqoob; Butt, Pinial Khan; Shah, Asadullah (Sindh University Press, 2020)
Abstract: Secure software development practices adoption could be the most influential factor for the future of software industry. Awareness and knowledge about security mechanisms and secure coding techniques plays a vital role in decision to consider security during software development by the software developers. This study aims to explore the security and secure software development awareness among software developers. The results of the study related to the use of secure software development methodologies showed a very low level of adoption level by the developers. It was revealed by the respondents that 82.72% respondents have never used any secure development methodology, about 13.67% respondents were using secure software development methodology in their software development from 1 to 4 years, 2.09% respondents using secure software development methodology in their software development from more than five years and only 1.57% respondents were using secure software development methodologies in their software development from less than a year. All the respondents were well aware of the software security but only 22.51% of the respondents were aware of the latest secure software development methodologies.